Reciprocal Relations between Work-Related Authenticity and Intrinsic Motivation, Work Ability and Depressivity: A Two-Wave Study - Emmerich, Astrid I.; Rigotti, Thomas (Frontiers in Psychology, 2017)
This study investigates the role of context-specific authenticity at work for work-related outcomes (intrinsic motivation, work ability) and depressivity. Furthermore reciprocal relations between work-related authenticity and healthy psychological functioning are investigated. Longitudinal data from 1,243 employees from 63 subsidiaries of a non-profit organization in the social sector were analyzed using multilevel structural equation modeling. Work-related authenticity at T1 predicted work ability and depressivity, but not intrinsic motivation at T2, about 6 months later. Work-related authenticity at T2 was predicted by intrinsic motivation and depressivity, but not by work ability at T1. We conclude that work-related authenticity and healthy psychological functioning are positively reinforcing each other. Thus, enabling employees to be authentic supposedly increases their well-being and is a pivotal opportunity for organizations to foster health and performance-related indicators like work ability and prevent negative health indicators like depressivity. At the same time, authenticity of employees can be fostered through workplace health promotion.